2014
DOI: 10.1002/jip.1414
|View full text |Cite
|
Sign up to set email alerts
|

Drop the Small Talk When Establishing Baseline Behaviour in Interviews

Abstract: The present experiment investigated the behavioural patterns of interviewees when comparing their baseline behaviour, prior to the interview, with their behaviour during the investigative interview. Similar to what has been advised in the police literature, the truthful baseline behaviour was established prior to the interview through non-threatening questions. The investigative part of the interview then followed in which the interviewee was aware that they would be assessed on whether they were lying. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 40 publications
4
38
0
Order By: Relevance
“…We found that similarity scores did not differ between truth tellers and liars for participants in the small talk condition. This result is similar to that obtained by Ewens et al (), who found that both truth tellers and liars showed differences in the amount of hard thinking and behavioural control between two phases of the interview. Our results therefore reject the efficacy of a small talk baseline procedure as proposed by Frank et al, () and by Inbau et al, () as in such a procedure truth tellers and liars would appear equally deceptive.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that similarity scores did not differ between truth tellers and liars for participants in the small talk condition. This result is similar to that obtained by Ewens et al (), who found that both truth tellers and liars showed differences in the amount of hard thinking and behavioural control between two phases of the interview. Our results therefore reject the efficacy of a small talk baseline procedure as proposed by Frank et al, () and by Inbau et al, () as in such a procedure truth tellers and liars would appear equally deceptive.…”
Section: Discussionsupporting
confidence: 91%
“…We found that similarity scores did not differ between truth tellers and liars for participants in the small talk condition. This result is similar to that obtained by Ewens et al (2014), who found that both truth tellers and liars showed differences in the amount of hard thinking and behavioural control between two phases of the interview.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To date, only two published studies have examined the utility of attending to a set of behaviours to establish and evaluate baseline, and these studies focused on baselining only for the purpose of detecting deception (Ewens, Vrij, Jang, & Jo, ; Palena, Caso, Vrij, & Orthey, ). Ewens et al () studied three types of cues that might constitute a baseline: gross measures of how hard a respondent appeared to be thinking, how much a respondent appeared to be controlling his/her hand and body movements, and how nervous the respondent appeared. The authors did not analyse nervousness because it could not be measured reliably.…”
Section: Introductionmentioning
confidence: 99%